Identification and Development of Items Comprising Organizational Citizenship Behaviors Among Pharmacy Faculty - Desselle, Shane P. (Am J Pharm Educ, 2016)
Objective. Identify behaviors that can compose a measure of organizational citizenship by pharmacy faculty. Methods. A four-round, modified Delphi procedure using open-ended questions (Round 1) was conducted with 13 panelists from pharmacy academia. The items generated were evaluated and refined for inclusion in subsequent rounds. A consensus was reached after completing four rounds. Results. The panel produced a set of 26 items indicative of extra-role behaviors by faculty colleagues considered to compose a measure of citizenship, which is an expressed manifestation of collegiality. Conclusions. The items generated require testing for validation and reliability in a large sample to create a measure of organizational citizenship. Even prior to doing so, the list of items can serve as a resource for mentorship of junior and senior faculty alike.